PERANCANGAN SISTEM PEMESANAN RENTAL MOBIL ALHAFID CAR BERBASIS WEB - Akrom Alhafid; Achmad Lutfi Fuadi (CV. Multi Kreasi Media, 2024)
Alhafid Car is a business engaged in the field of transportation for car rental. In daily business processes, the process of leasing transactions and data collection has not used a computerized system. Managers still use logbooks for recaps and customer tenant transactions. This creates security issues including allowing data to be lost or damaged. The purpose of writing this paper is to design and implement the design of a web-based alhafid car rental booking system. The research method used by the author in preparing this paper is the waterfall method. Based on the research results obtained from the application of the web-based Alhafid Car rental booking system design, it can help and provide convenience for customers in the online vehicle rental process and make it easier for rental managers to collect data on vehicle rental transactions.